Developing a Fantasy Text Module for Indonesian Secondary ‎Schools: A Research and Development Study - Dandy Arison Saputra; Robi Irawan; Riko Pirmansyah (Yayasan Darussalam Bengkulu, 2023)
The study aims to develop and validate a fantasy text module for Indonesian language instruction in junior secondary schools. Employing a research and development (R&D) design adapted from Borg and Gall, the study involved two Indonesian language teachers at SMP Negeri 12 Bengkulu and three expert validators in content, language, and media. Data were collected through teacher needs questionnaires, expert judgment sheets, and iterative prototype revisions, then analyzed using descriptive statistics. The results indicate that teacher needs assessments scored 92% and 72%, confirming the demand for supplementary materials, while expert validation scores ranged from 70% to 87%, with an overall feasibility rating of 77.3% in the “good” category. Revisions focused on improving conceptual mapping, evaluation tasks, linguistic accuracy, and graphic design to enhance clarity and usability. These findings demonstrate that the developed module is pedagogically sound and practically applicable, effectively supporting students’ ability to write fantasy texts in alignment with the 2013 curriculum. The study concludes that fantasy text modules not only enrich literacy instruction but also foster imagination and moral values, offering a creative and contextually responsive resource for Indonesian language education in junior secondary schools.